Applying a survival sex hierarchy to the commercial sexual exploitation of children: a trauma-informed perspective. Issue 3 (27th May 2019) - McDonald, Amber R.; Middleton, Jennifer
ABSTRACT: Commercial sexual exploitation of children (CSEC) is not a new problem. However, due to the evolution of its conceptualization, CSEC has garnered the attention of child welfare professionals and communities across the nation. Many victims tend to come from vulnerable populations with a serious history of previous abuse, suggesting a significant overlap with youth involved in the child welfare system. Furthermore, commercial sexual exploitation (CSE) results in significant psychological trauma and negatively impacts development. Child welfare agencies are tasked with addressing the problem through screening, intervention, and treatment. Due to the role that trauma plays in both predisposing youth to CSE and its significant, complex consequences, a trauma-informed approach to working with CSEC is imperative. In this article, the authors apply a survival sex hierarchy model to CSEC, discuss its goodness of fit with the tenets of trauma-informed care, and identify clear implications for trauma-informed child welfare practice and policy.